Teachers’ visual inspection of Curriculum-Based Measurement progress graphs: An exploratory, descriptive eye-tracking study - van den Bosch, Roxette M.; Espin, Christine A.; Sikkema-de Jong, Maria T.; Chung, Siuman; Boender, Priscilla D. M.; Saab, Nadira (Frontiers in Education, 2022)
In this exploratory descriptive study, we use eye-tracking technology to examine teachers’ visual inspection of student progress graphs. More specifically, we examined which elements of the graph received the most visual attention from teachers, and to what extent teachers viewed graph elements in a logical sequence. We also examined whether graph inspection patterns differed for teachers with higher- vs. lower-quality graph descriptions. Participants were 17 fifth- and sixth-grade teachers. Participants described two progress graphs while their eye-movements were registered. In addition, data were collected from an expert to provide a frame of reference for interpreting the teachers’ eye-tracking data. Results revealed that, as a group, teachers devoted less visual attention to important graph elements and inspected the graph elements in a less logical sequence than did the expert, however, there was variability in teachers’ patterns of graph inspection, and this variability was linked to teachers’ abilities to describe the graphs. Directions for future studies and implications for practice are discussed.